PEMBIMBINGAN INTENSIF MATERI ALGORITMA DAN PEMOGRAMAN DASAR TERHADAP PESERTA OLIMPIADE SAINS NASIONAL BIDANG INFORMATIKA TINGKAT KOTA PADA SMA NEGERI 2 KOTA JAMBI - Rosario, Maria; Arief Hermawan Sutoyo, Mochammad; Siswanto, Agus; Pratama, Yovi; Feranika, Ayu; Emelia, Shinta (Jurnal Pengabdian Masyarakat UNAMA, 2024)
Intensive guidance on algorithms and basic programming involves OSN participants from SMA Negeri 2 Jambi City, who have passed the school selection. In the Guidance, they will be given in-depth guidance on algorithm concepts, data structures and basic programming using C++. The importance of this coaching lies in preparing OSN participants to be able to face national level exams with confidence. By increasing their understanding and mastery of basic algorithms and programming, it is hoped that participants can produce innovative and effective solutions in dealing with various problems tested in OSN Informatics. This coaching also creates a learning environment that supports the growth of participants as individuals who are ready to compete at the national level in the field of Informatics.